CYP gene family variants as potential protective factors in drug addiction in Han Chinese. (August 2016) - Zhang, Hongxing; Yang, Qi; Zheng, Wenkai; Ouyang, Yongri; Yang, Min; Wang, Fengjiao; Jin, Tianbo; Zhang, Ji; Wang, Zhenyuan
Abstract: Background: There is growing evidence that genetic factors also contribute to drug addiction. The human cytochrome P450 has shown special interest because of pharmacokinetic variation in different individuals and populations, which is largely determined by the relevant genes. The present study aimed to investigate the polymorphism of the CYP/addicts relationship. Methods: We genotyped 13 tag single‐nucleotide polymorphisms (tSNPs) from three genes, including 692 cases and 700 controls. Sequenom MassARRAY RS1000 (Sequenom, Inc., San Diego, CA, USA) was used for SNP genotyping. Statistical analysis of the association between tSNPs and drug addiction was performed using the chi‐squared test and SNP Stats software (http://bioinfo.iconcologia.net ). Results: The T/T genotype of rs2242480 in CYP3A4 was associated with decreased risk in the recessive model ( p = 0.0002). Allele frequency at rs3743484 in CYP1A2 showed significant differences between addicts and controls ( p = 0.046; odds ratio = 0.80; 95% confidence interval = 0.65–1.00). In genetic model analyses, the minor C allele of rs3743484 in CYP1A2 was associated with a reduced risk of drug addiction based on analysis using codominant and additive models ( p = 0.027 dominant model; p =0.038 additive model). Conclusions: Our findings show that at allelic and genotypic level polymorphisms in CYP3A4 and CYP1A2 are significantly associated with a reduced risk of drug addiction in X'ian Han Chinese individuals. However, this result needs to be confirmed in additional studies. Copyright © 2016 John Wiley & Sons, Ltd.